Analysis of Organizational Development Through the Diagnostic Process at LPP RRI Banjarmasin - Nurul Magfirah; Nursilla; Shanty Komalasari (Journal of Social and Industrial Psychology, 2024)
This research aims to analyze organizational development at LPP RRI Banjarmasin through a diagnosis process. A quantitative approach was used involving 40 employees from various fields as the population. Apart from that, various sources from scientific journals, books and other references were used to support this research. Data were collected through a questionnaire covering seven main variables: goals, structure, leadership, relationships, rewards, supporting mechanisms, and attitudes towards change. The diagnosis process involves stages of orientation, gathering information, analyzing data, and making conclusions for improvement. The research results show that effective organizational development requires a deep understanding of organizational culture, adaptation to environmental changes, and commitment from leaders and employees. Organizational diagnosis helps identify core problems that hinder effectiveness and efficiency, and designs strategies to improve organizational performance. This study emphasizes the important role of leadership in organizational development and provides recommendations for achieving strategic goals more efficiently.